How does climate exacerbate root causes of conflict in Uganda? Climate Security Pathway Analysis - Madurga Lopez, Ignacio M.; Dutta Gupta, Tanaya; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Uganda, using an impact pathway analysis. Two main impact pathways are identified: 1) Resource availability and access in Kasese; 2) Livelihood and food insecurity in Karamoja .